2020
DOI: 10.1088/2053-1591/ab6c90
|View full text |Cite
|
Sign up to set email alerts
|

Destabilization of PVA-stabilized Ag NPs: color changes at low aqueous concentrations, induced by aggregation and coalescence

Abstract: Aqueous concentrations of poly(vinyl alcohol) (PVA)-stabilized ∼10 nm silver nanoparticles (Ag NPs), in the 1000 ppm concentration range, have been shown to be highly stable at elevated temperatures. However, lower concentrations of these NPs undergo color changes, without precipitation, when heated or when held for extended periods of time at room temperature. We have studied their optical and morphological changes at 80°C, using UV-vis spectra and TEM, and found that their color, at a concentration of 10 ppm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
3
1
0
Order By: Relevance
“…This is consistent with the TEM data and will be discussed later. There is no aggregation of Ag NPs during the reaction and alloying because the appearance of a new peak at 450–600 nm [ 45 , 46 , 47 ] signifying aggregation was not observed; this is consistent with the TEM photomicrographs. The dependence of the SPR peak intensity on time and Cu 2+ concentration ( Figure 2 a and Figure 3 ) indicates that the greater the Cu concentration, the greater the SPR intensity decrease.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This is consistent with the TEM data and will be discussed later. There is no aggregation of Ag NPs during the reaction and alloying because the appearance of a new peak at 450–600 nm [ 45 , 46 , 47 ] signifying aggregation was not observed; this is consistent with the TEM photomicrographs. The dependence of the SPR peak intensity on time and Cu 2+ concentration ( Figure 2 a and Figure 3 ) indicates that the greater the Cu concentration, the greater the SPR intensity decrease.…”
Section: Discussionsupporting
confidence: 83%
“…There is no aggregation of Ag NPs during the reaction and alloying because the appearance of a new peak at 450–600 nm [ 45 , 46 , 47 ] signifying aggregation was not observed; this is consistent with the TEM photomicrographs.…”
Section: Discussionsupporting
confidence: 83%
“…While the color of Ag NP-coated fabrics, which changes from beige to light brown after running for one month, is principally caused by Ag NP aggregation, which is assisted by air flow. Ag ion-coated fibers, without and with PVP-PVA stabilizers, change from white (or light yellow) to light brown after running for one month, caused by Ag NP aggregation, which we have found previously [ 73 ]. This means that no aggregation occurred for the AgCu NP-coated fabrics by air flow, suggesting that the adhesion of AgCu NPs to the fabric is stronger than that of Ag NPs and Ag ions.…”
Section: Discussionsupporting
confidence: 65%
“…UV–visible spectroscopy was carried out to investigate the morphologies of the medium after each excitation, as shown in Figure 5 c. The results reveal that the absorption peak of the medium diminished when the number of excitations increased. According to the Beer–Lambert law, the absorption peak of UV–visible spectroscopy is a linear function of Ag NP concentration at room temperature [ 36 ], so Figure 5 c implies a small decrease in NP concentration in the range of 0~20 ppm. In order to investigate the relationship between the radiation ability of the Ag NP suspension and its NP concentration, we measured the terahertz radiation from the quasispherical Ag NPs with different NP concentrations below 20 ppm, as shown in Figure 5 d. It was observed that the terahertz radiation showed an upward trend as the laser power increased, but no direct dependence between the NP concentration and terahertz radiation was established.…”
Section: Resultsmentioning
confidence: 99%
“…The results reveal that the absorption peak of the medium diminished when the number of excitations increased. According to the Beer-Lambert law, the absorption peak of UV-visible spectroscopy is a linear function of Ag NP concentration at room temperature [36], so Figure 5c implies a small decrease in NP concentration in the range of 0~20 ppm. In order to investigate the relationship between the radiation ability of the Ag NP suspension and its NP concentration, we measured the terahertz radiation from the quasispherical Ag NPs with different NP concentrations below 20 ppm, as shown in Figure 5d.…”
Section: Quasispherical Ag Npsmentioning
confidence: 98%